Aspek Konsumsi Ultra Processed Food dengan Kejadian Overweight pada Anak Usia Sekolah Dasar di SDN V Mojosongo Surakarta - Nabilah Beryl Nathaniela; Dyah Intan Puspitasari; Farida Nur Isnaeni (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
This study aims to analyze the relationship between the level of UPF (Ultra Process Food) consumption and the incidence of overweight in elementary school children at SDN V Mojongso Surakarta. This study was conducted using an observational quantitative method using analytical with a case-control approach. The subjects of this study were 4th and 5th grade students at SDN V Mojosongo Surakarta with a population of 221 students and a total sample of 80 children selected using a simple random sampling technique. Of the 80 respondents, there were 40 boys and 40 girls (50% each). Analysis based on gender showed that the proportion of boys who were overweight (55%) was slightly higher than girls (45%). The results of the Chi-square correlation analysis showed a significant relationship between Ultra-Processed Food (UPF) consumption and the incidence of overweight in elementary school students (p<0.05; p-value = 0.000). Students with excessive UPF consumption (>50% of the Adequate Nutritional Intake) had a 58 times higher risk of being overweight compared to students with sufficient UPF consumption. Therefore, cooperation between parents and schools is needed to form healthy eating habits in children at home. Children are also encouraged to maintain regular eating and rest patterns to support optimal development and prevent the risk of being overweight